Análise da implementação da política de educação permanente em saúde em uma região do Estado de São Paulo - Ribeiro, Cristiane (2016)
The object of this research is to analyze how the process of actions implementation of Permanent Education in Health (EPS) works in a region of São Paulo, on the assumption that the Unified Health System (SUS) has responsibility for ordering and training Human Resources - HR for health. In addition, it is still far from a professional training and working process reorganization to promote transformation and reorientation of attention, care and management models. This is an exploratorydescriptive study of qualitative approach, whose main objective is to analyze through documental research, public documents of the municipalities relating to EPS actions, emphasizing the EPS deployment and implementation in the territory of the Regional Health Department III - DRSIII Araraquara / São Paulo. The analysis was guided by the theoretical reference of EPS and Primary Health Care (ABS), and the results were presented by categories. The guiding documents such as the Regional Action Plan for Permanent Education in Health (PAREPS) and the Health Maps were identified, and submitted to documental analysis with thematic content technique, which enabled to identify how the EPS actions is being implemented in a region of the state of São Paulo. Based on qualitative analysis, the results, organized and presented by health region, show their characterization as well as the needs and proposals identified in each PAREPS within the period of 2008 to 2015. Through the analysis, it is apprehended that the EPS can be considered a “management and intervention strategy” that suggests a revision of management, attention, training workers and social participation practices in a critical and reflective perspective, making articulations between training and the working world, and, supporting significant learning, in a learning process that could produce senses and meanings in order to contribute to the social transformation of reality.